Comparison between commonly practised techniques of flexor tendon repair considering the preferences of surgeons in Malaysia with biomechanical analysis - Shalimar Abdullah; Rahul Lingam; Walter Gryczewski; Md Rayhan Ali Mollah; Elaine Soh; Jamari Sapuan; Tanvir Rahman Faisal; Ahmed Suparno Bahar Moni (Journal of Orthopaedic Reports)
Background: Flexor tendon injuries are among the most challenging Orthopaedic conditions to manage. Early repair and physical therapy are crucial for good outcome as well as the repair method. Objective: This study aims to explore the surgical preference of orthopaedic and hand surgeons of Malaysia integrated with biomechanical analysis of the common repair techniques to ensure quality and early outcome of various techniques. Methods: A survey was distributed among the orthopaedic and hand surgeons at annual Orthopaedic conference in 2019 and Hand surgery conference in 2021 to explore their preferences of flexor tendon repair. For biomechanical study, forty tendon samples were obtained from the amputated lower limbs and were repaired using one of the four popular 4-strands repair methods. Samples were then biomechanically tested. Three variables were monitored, core suture placement time, force required for 2-mm gap creation, and ultimate tensile strength. Statistical analysis was conducted to examine an association between core tendon repair techniques and the load required to cause repair failure. Results: Among the respondents of the survey, there was no consensus for the technique of the repair, however most of the respondents utilized a 4-strand technique using 4/0 Prolene suture. Inner and outer Kessler method was found to be the quickest to place at 5.77 ± 0.55 min. The Adelaide (AD) method required the largest maximum force to fail at 42.07 ± 14.57 N and the highest force for 2 mm gap at 29.07 ± 15.43 N. Conclusions: Flexor tendon repair is a technically demanding procedure requiring a balance between surgeons’ skill and technique and strength of the repair. As all 4-strands repairs can withstand the 10 N load generated by mildly resisted active flexion and extension of the fingers, post operative therapy could be launched immediately after the repair.